2015
DOI: 10.1038/srep17944
|View full text |Cite
|
Sign up to set email alerts
|

Anti-sense DNA d(GGCCCC)n expansions in C9ORF72 form i-motifs and protonated hairpins

Abstract: The G4C2 hexanucleotide repeat expansion mutation (HREM) in C9ORF72, represents the most common mutation associated with amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Three main disease mechanisms have been proposed to date: C9ORF72 haploinsufficiency, RNA toxicity, and accumulation of dipeptide repeat proteins. Pure GC content of the HREM potentially enables the formation of various non-B DNA structures such as G-quadruplexes and i-motifs. These structures are proposed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 34 publications
3
71
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ The precise information about the structure of the hairpin-like structure is not yet known. However, it has been reported that a hairpin-like structure can form from the C-rich strand of C9ORF72 consisting of a C 4 G 2 repeat 44 . This hairpin structure is formed with Watson-Crick base pairing of the cytosine and guanine bases, and may further fold into a tertiary structure.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ The precise information about the structure of the hairpin-like structure is not yet known. However, it has been reported that a hairpin-like structure can form from the C-rich strand of C9ORF72 consisting of a C 4 G 2 repeat 44 . This hairpin structure is formed with Watson-Crick base pairing of the cytosine and guanine bases, and may further fold into a tertiary structure.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas C9ORF72-S can form G-quadruplexes [46,55,116] that are known to regulate transcription and gene expression [150], the C-rich C9ORF72-AS repeats may not form similar structures. Instead, the G 2 C 4 expansions in C9ORF72-AS may form a C-rich motif [65] that likely affects genome stability and transcription [1]. Notably, an A-form-like double-helix with a tandem C:C mismatch has been observed in a crystal structure of the C9ORF72-AS repeat expansion, suggesting that different structural forms of C9ORF72-AS might regulate disease progression [38].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…The intronic (G 4 C 2 ) hexanucleotide repeat expansion within the C9ORF72 gene has been shown to be the main genetic feature of ALS 14 16 . As well as giving rise to exotic DNA features such as G-quadruplexes and i-motifs 17 , 18 , the expanded repeats undergo both aberrant and unconventional processing (reviewed in Vatovec et al . 19 ), which further supports disease-associated changes in RNA metabolism as a core mechanism in ALS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%